Molybdenum Isomorphously Substituted Decatungstates as Robust and Renewable Photocatalysts for Visible Light‐Driven Oxidation of Hydrocarbons by Molecular Oxygen. Issue 9 (3rd March 2021) - Yang, Bo; Zhang, Huanhuan; Wan, Feifei; Deng, Youer; Jiang, Dabo; Zhang, Qiao; Liu, Yachun; Zhang, Chao; Fu, Zaihui
Abstract: This article reveals that molybdenum (Mo) heteroatoms isomorphously substituted decatungstates (Mo–DTs) can be conveniently synthesized via copolymerization of tungstate and molybdate in acidic solution. A series of characterizations support that the incorporated Mo heteroatoms play crucial roles in improving the redox capacity and visible light harvesting efficiency of Mo–DTs, especially the photo‐excited probability and lifetimes, so that the novel Mo–DTs exhibit a remarkably enhanced photo‐catalytic efficiency in the visible‐light‐triggered selective oxidation of inert hydrocarbons by O2 under mild conditions. In the photo‐oxidation of cyclohexane under continuous visible light irradiation for 30 h, the best 1 % Mo–DT can achieve 44.8 % conversion and 89.7 % cyclohexanone selectivity in the presence of 2 M HCl, and the regenerated catalyst after simple hydrothermal treatment has excellent reusability. This is the first successful example of incorporating Mo atoms into the skeleton of non‐lacunary DTs, which has special significance for expanding the application of DTs in visible‐light‐catalysis. Abstract : A real sun‐trap : The firstly synthesized molybdenum isomorphously substituted decatungstate (Mo–DT) shows a significantly enhanced photocatalytic performance for visible light‐triggered selective oxidation of hydrocarbons by O2 as the incorporated Mo plays vital roles in improving its redox capacity and photophysical and chemical properties.